Economic Resilience Index and Studying Its Effects on Iran’s Economic Growth - Mansour Zaranezhad; Ebrahim Anvari; HamidReza Halafi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Reviewing and criticizing theories of economic growth can help researchers choose the main factors affecting economic growth rate. In this research, the effect of the resilience index on economic growth in Iran has been evaluated by reviewing and criticizing the growth ideas and examining the factors affecting them. Research findings have confirmed the positive impact of this index on Iran's economic growth. The implementation of various scenarios showed that after the occurrence of shocks, the simulated economic growth had a consistent and upward trend. Implementing effective financial, currency, and monetary policies to reduce the misery rate, narrowing the scope of government activities, reducing the ratio of budget deficit to the GDP, and making reforms to the administrative and judicial infrastructure of the country are some of the suggestions that could pave the way for the promotion of economic resilience and strengthening the economic growth of Iran.